2020
DOI: 10.1177/1708538120929506
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous versus staged carotid artery stenting and coronary artery bypass graft for patients with concomitant severe coronary and carotid artery stenosis: A systematic review and meta-analysis

Abstract: Background Coronary artery disease requiring coronary artery bypass graft (CABG) frequently coexists with critical carotid stenosis. The most optimized strategy for treating concomitant carotid and coronary artery disease remains debatable. Objective The aim of this meta-analysis was to compare synchronous CAS and CABG versus staged CAS and CABG for patients with concomitant coronary artery disease and carotid artery stenosis in terms of peri-operative (30-day) and long-term clinical outcomes. Methods This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…Even within the carotid artery stenting group, whether to do a staged procedure or a synchronous one remains debatable. In another meta-analysis including four observational studies comparing staged and concomitant carotid artery stenting and CABG, Tzoumas et al reported an increased risk of 30-day stroke in the concomitant group as compared to the staged one [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even within the carotid artery stenting group, whether to do a staged procedure or a synchronous one remains debatable. In another meta-analysis including four observational studies comparing staged and concomitant carotid artery stenting and CABG, Tzoumas et al reported an increased risk of 30-day stroke in the concomitant group as compared to the staged one [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Major adverse cardiac and cerebrovascular events (MACCE) within this patient collective are driven by myocardial infarction, stroke or transient ischemic attack (TIA) and an elevated all-cause mortality [4][5][6]. With respect to the optimal approach for patients with concomitant cardiac vitium and internal carotid stenosis, several concepts were analyzed [7,8]. The approach with respect to timing and modality of the carotid revascularization is subject The analysis of intraoperative characteristics for the no-MACCE and MACCE groups is shown in Table 2 with respect to number of carotid endarterectomy using a patch, coronary artery bypass grafting, aortic valve replacement, mitral valve replacement, mitral valve repair, tricuspid valve repair, atrial ablation, atrial exclusion, concomitant surgery, the use of cardio-pulmonal bypass, cardiopulmonary bypass time, aortic cross clamp time, operation time and number of intraoperatively used intra-aortic balloon pump supports.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Several approaches and concepts were analysed for this specific cohort of patients. 6,7 The timing and the modality of carotid revascularization were controversially discussed and should be based on clinical presentation, level of emergency, and severity of carotid and coronary artery diseases. Current guidelines on myocardial revascularization recommend for patients scheduled for coronary artery bypass grafting (CABG) with a history of stroke/TIA (<6 months) and 50–99% carotid stenosis that carotid revascularization should be considered (Class IIa, Level B).…”
Section: Introductionmentioning
confidence: 99%